Core self-evaluations and psychological health among nurses: the mediating role of work-family conflict - Mohd Hanifa, Suzana; Ismail, Zanariah (Secholian Publication, 2021)
Changes in the workforce demographics have led many individuals, particularly women, to experience work-family conflict as they juggle between their work and family roles. However, not much is known about the role of work-family conflict in the relationship between positive personality traits, namely, core self-evaluations and psychological health, among nurses. Thus, this study presents a model which examines the impact of core self-evaluations on nurses’ psychological health (i.e., psychological distress and life satisfaction) and whether work-family conflict will have a mediating influence on such relationship. Based on the ecological systems theory and the conservation of resources theory, the model proposes that core self-evaluations will have a direct effect on work-family conflict, life satisfaction and psychological distress in nurses. In addition, it is hypothesised that core self-evaluations will have an indirect effect on life satisfaction and psychological distress through work-family conflict. Finally, this model highlights the importance of core self-evaluations as personal resources that can protect nurses from work-family conflict and enhance their psychological health.